2005
DOI: 10.1002/em.20178
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of arsenic in Drosophila melanogaster and the genotoxicity of dimethylarsinic acid in the Drosophila wing spot test

Abstract: Inorganic arsenic is nongenotoxic in the Drosophila melanogaster wing somatic mutation and recombination test (SMART). Recent evidence in mammalian systems indicates that methylated metabolites of arsenic are more genotoxic than inorganic arsenic. Thus, we hypothesized that inorganic arsenic is nongenotoxic in Drosophila because they are unable to biotransform arsenic to methylated forms. In the present study, we fed trivalent and pentavalent inorganic arsenic to Drosophila larvae and adults and measured the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…2 Methylene arsenic compounds have been shown to be genotoxic. 3 The consumption of agricultural products irrigated through natural water having arsenic can reach people as it is accumulated in the food chain. 4 More than 80% of arsenic compounds which are toxic and tasteless, as additives in metal alloys and glass are used for products such as semiconductors and dyes.…”
Section: Introductionmentioning
confidence: 99%
“…2 Methylene arsenic compounds have been shown to be genotoxic. 3 The consumption of agricultural products irrigated through natural water having arsenic can reach people as it is accumulated in the food chain. 4 More than 80% of arsenic compounds which are toxic and tasteless, as additives in metal alloys and glass are used for products such as semiconductors and dyes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies with Drosophila as well as with bacterial and mammalian cell mutation assays have shown that arsenic alone fails to behave as a point mutagen and thus it was classified largely as an epigenetic carcinogen (24)(25)(26). However, in another recent study, evidence was reported on the chromosomal aberrations in bone marrow cells of arsenic exposed rats (13).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to arsenic has been observed to cause prostate cancer in humans and liver cancer in mice [18,19]. Mutation caused by arsenic has not been evident till date, but epigenetic changes by altering methylation of promoter of genes are superfluous in the literature [20][21][22]. Arsenic has also been shown to cause hypermethylation of tumor suppressor genes [18].…”
Section: Resultsmentioning
confidence: 99%